The Philosophy of Traditional Islamic Education: A Study of Pesantren al-Maqbul in Indonesia in Contextual Dialogue with the Islamic Educational Tradition in Libya - Sulton, Ahmad; Masuwd, Mowafq Abrahem; Sirait, Sangkot; Arif, Mahmud (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This study examines the philosophy of traditional Islamic education with a particular focus on Pesantren al-Maqbul in Indonesia, while conceptually comparing it to traditional Islamic educational institutions in Libya. It employed a qualitative comparative method. For data analysis, an inductive-philosophical approach was used. The findings reveal that the sustainability of the traditional educational system at Pesantren al-Maqbul is inextricably linked to its philosophical foundations. Ontologically, the pesantren adheres to a monistic worldview, positioning revelation (the Qur’an and Hadith) as the sole authoritative source of knowledge. Epistemologically, it employs the Bayani approach—a method characterized by rigorous textual reasoning—in teaching and learning. From an axiological perspective, the pesantren adopts an Irfani orientation, emphasizing the cultivation of ethics, proper conduct (adab), and spiritual dimensions. This approach closely resembles the traditional Islamic education model in Libya, highlighting the authority of revealed texts, the halaqah method of instruction, and Sufi values. The similarities suggest that traditional Islamic educational philosophy is grounded in universally shared principles despite differing geographical and social contexts. The study concludes that traditional educational systems remain relevant due to their solid philosophical foundations and capacity to adapt to contemporary challenges contextually.